From aardvark to zucchini : [videorecording (DVD)] : my very own alphabet of prayers - Mead, David (Creative Communications for the Parish ; Distributed by Vision Video, 2004)
"Filled with songs and rhymes, this animated video is an entertaining and educational introduction to prayer for preschoolers and their parents"--Container.